2015
DOI: 10.1002/jts.21990
|View full text |Cite
|
Sign up to set email alerts
|

Equine‐Assisted Therapy for Anxiety and Posttraumatic Stress Symptoms

Abstract: We tested the efficacy of the Equine Partnering Naturally(©) approach to equine-assisted therapy for treating anxiety and posttraumatic stress disorder (PTSD) symptoms. Participants were 16 volunteers who had experienced a Criterion A traumatic event, such as a rape or serious accident, and had current PTSD symptoms above 31 on the PTSD Checklist (PCL-S; Weathers, Litz, Herman, Huska, & Keane, ). Participants engaged in tasks with horses for 6 weekly 2-hour sessions. Immediately following the final session, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 22 publications
2
59
0
3
Order By: Relevance
“…Historical trauma experienced by American Indians and other groups is often overlooked in the trauma literature, but youth who participated in a multi-component intervention that included EFT showed improvement in cultural identity, coping strategies, quality of life and social adjustment (Goodkind et al, 2012). Of the five studies with samples of adults, one included veterans (Nevins et al, 2012) two included women who had experienced interpersonal violence (Schroeder & Stroud, 2015;Shambo et al, 2010), and one included men and women with various traumatic events (Earles et al, 2015). Improvement was found in PTSD symptoms, mindfulness, depression, dissociative symptoms, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Historical trauma experienced by American Indians and other groups is often overlooked in the trauma literature, but youth who participated in a multi-component intervention that included EFT showed improvement in cultural identity, coping strategies, quality of life and social adjustment (Goodkind et al, 2012). Of the five studies with samples of adults, one included veterans (Nevins et al, 2012) two included women who had experienced interpersonal violence (Schroeder & Stroud, 2015;Shambo et al, 2010), and one included men and women with various traumatic events (Earles et al, 2015). Improvement was found in PTSD symptoms, mindfulness, depression, dissociative symptoms, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…'Desta forma, o contato com o animal pode desencadear respostas orgânicas que diminuem o estado de alerta e apreensão constantes em um indivíduo ansioso (NEPPS et al, 2014). Foi observado em estudo prévio que a prática de equoterapia durante seis semanas (uma sessão semanal com duração de duas horas) promoveu diminuição nos sintomas de ansiedade em pacientes com síndrome de estresse póstraumático (EARLES et al, 2015). No presente relato, não foi observada diminuição significativa na ansiedade-traço do paciente, uma vez que esta é menos passível de modificação, já que é uma característica da personalidade do indivíduo (SPIELBERGER et al, 1970).…”
Section: (Muitíssimo)unclassified
“…A single-group pretest-posttest design with 16 adults with post traumatic stress disorder (PTSD) found that 6 weekly 2-h sessions of equine-assisted therapy reduced symptoms of PTSD, emotional trauma, anxiety, alcohol use, and depression. Mindfulness increased, but physical health was unchanged [36]. Another single-group pretestposttest design found that regular AAT with a dog decreased loneliness in 21 geriatric nursing home residents [37].…”
Section: Quasi-experimental Studiesmentioning
confidence: 99%